Managing hyponatremia: fast or slow? why, when, how, and controversies - Kamel S Kamel; Ziv Harel; Martin Schreiber (Clinical Kidney Journal, 2026)
Abstract Hyponatremia is the most common electrolyte disorder encountered in clinical practice. Its management is challenging because treatment must balance the risk of cerebral edema in acute hyponatremia against the risk of osmotic demyelination syndrome (ODS) from overly rapid correction of chronic hyponatremia. Recent observational studies have questioned current correction limits, prompting renewed debate regarding optimal management. This narrative review presents a physiology-based approach to the evaluation and treatment of hyponatremia. Acute hyponatremia may cause life-threatening cerebral edema because cerebral adaptation is incomplete, whereas chronic hyponatremia is characterized by the loss of intracellular electrolytes and organic osmolytes that limit brain swelling but increase vulnerability to osmotic injury during correction. Because the duration of hyponatremia is often uncertain, management should be guided primarily by neurological manifestations rather than duration alone. We propose a systematic treatment approach based on neurological severity, the duration of hyponatremia when definitively known, and the patient’s risk of neurological injury, balancing the immediate danger of cerebral edema against the risk of ODS. We critically review the evidence underlying current correction limits and recent observational studies reporting that ODS is uncommon, inconsistently associated with overly rapid correction, and that slower correction has been associated with higher mortality. We conclude that, until higher-quality evidence becomes available, conservative correction limits for management of chronic hyponatremia remain appropriate, with correction not exceeding 10 mmol/L in 24 hours (18 mmol/L in 48 hours) in average-risk patients, targeting a rise of 4–8 mmol/L/day, and 8 mmol/L in 24 hours in patients at high risk for ODS, targeting a rise of 4–6 mmol/L/day.